EDUCAÇÃO CIBERCULTURAL - Carvalho, Felipe; Edméa Santos; Mariano Pimentel; Marcos Vinícius Dias de Menezes; Wallace Carriço de Almeida; Tania Lucía Maddalena (Revista Docência e Cibercultura, 2024)
Configurações<a id="cell-2479-identification-edit-button-66269c5d69a1e" class="pkp_controllers_linkAction pkp_linkaction_edit pkp_linkaction_icon_" href="https://www.e-publicacoes.uerj.br/re-doc/call/grid/issues/future-issue-grid/edit-issue?issueId=2479">v. 8 n. 3 (2024): Elas/es nas redes: decolonialidade nas pesquisas e nas docências sobre/na/com a cultura digital